Chlamydia trachomatis infection and sexual behaviour among female students attending higher education in the Republic of Ireland - Vellinga Akke; O'Donovan Diarmuid; Glacken Marita; Cormican Martin; Brennan Wendy; O'Connell Emer; Cahill Niall; Lysaght Fionnguala; O'Donnell Joan (BMC, 2009)
Abstract Background There are no prevalence data on Chlamydia trachomatis relating to female students attending higher education available for the Republic of Ireland. This information is required to guide on the necessity for Chlamydia screening programmes in higher education settings. This research aimed to determine the prevalence of and predictive risk factors for Chlamydia trachomatis genital infection among female higher education students in Ireland. Methods All females presenting during one-day periods at Student Health Units in three higher education institutions in two cities in the Republic of Ireland were invited to participate. Participants completed a questionnaire on lifestyle and socio-demographic factors and provided a urine sample. Samples were tested for C. trachomatis DNA by a PCR based technique (Cobas Amplicor, Roche). To examine possible associations between a positive test and demographic and lifestyle risk factors, a univariate analysis was performed. All associations with a p value < 0.05 were included in a multivariate logistic regression analysis. Results Of the 460 sexually active participants 22 tested positive (prevalence 4.8%; 95% CI 3.0 to 7.1%). Variables associated with significantly increased risk were current suggestive symptoms, two or more one-night stands and three or more lifetime sexual partners. The students displayed high-risk sexual behaviour. Conclusion The prevalence of C. trachomatis infection and the lack of awareness of the significance of suggestive symptoms among sexually experienced female students demonstrate the need for a programme to test asymptomatic or non-presenting higher education students. The risk factors identified by multivariate analysis may be useful in identifying those who are most likely to benefit from screening. Alcohol abuse, condom use, sexual behaviour (at home and abroad) and, knowledge of sexually transmitted infections (STIs) (including asymptomatic nature or relevant symptoms) were identified as target areas for health promotion strategies. These strategies are needed in view of the high-risk sexual activity identified.